The impact of contextual teaching and learning on elementary students’ ability to solve mixed arithmetic word problems - Titik Rahmawati; Sucipto; Yuni Listiana (Bulletin of Educational Management and Innovation, 2026)
Background: The challenges of Mathematics learning in elementary schools include both the conceptual understanding and students capacity to solve a word problems. The solution can thus be through contextualised and meaningful models of learning that help students understand. Purpose: This research aims to examine the effect of the Contextual Teaching and Learning (CTL) model on understanding concepts and solving story problems in mixed arithmetic operations. Method: This study was an experimental study with unequal control group (52 students). Data were collected as result of the tests, and subsequently analyzed using the Wilcoxon test to verify any differences before and after treatment. Findings:  There was a statistical significant improvement in multiple areas after the CTL model has been initiated. The average conceptual understanding improved from 63.85 to 84.62 with p value0.000 (<0.05) Next, for the skill to solve mathematical problems gradually increased from 10.00 to 13.62 with a significancy value of 0.000 These results show that the CTL model has a very good effect on the development of students' conceptual understanding and mathematical problem solving abilities.